A backstepping approach to ship course control - Witkowska, Anna; Tomera, Mirosław; Śmierzchalski, Roman (Zielona Góra: Uniwersytet Zielonogórski)
As an object of course control, the ship is characterised by a nonlinear function describing static manoeuvring characteristics that reflect the steady-state relation between the rudder deflection and the rate of turn of the hull. One of the methods which can be used for designing a nonlinear ship course controller is the backstepping method. It is used here for designing two configurations of nonlinear controllers, which are then applied to ship course control.
Keywords: backstepping; nonlinear control; genetic algorithms; ship control; Lyapunov function